Analysis of Microwave Heating Process for Demulsification of Water-in-Crude Oil Emulsions - Akbari, Sweeta; Nour, A. H.; Fayaz, Fahim; Halimi, Mohammad Sediq; Nazari, Ahmadshah (AENSI Publishing, 2016)
In this investigation, the process of microwave heating technology was evaluated to measure the effect of some important parameters such as dielectric properties (έ and ɛʺ), rate of temperature increase (dT/dt), volume rate of heat generation (Qmw), wavelength (λ) and penetration depth (Dp) during the microwave irradiation on crude oil emulsions. Two types of Malaysian crude oil mixed together at a volume ratio of 50-50% and applied for further investigations. In order to ensure the efficiency of the process, the improvement of existing techniques and the development of new technology different ratios of water and oil were utilized to prepare the emulsions of water-in-crude oil (W/O). The emulsion samples were heated under 360 watt and 540 watt for 3 to 5 minutes. The findings of the microwave heating demulsification showed that higher microwave power (540 watt) along with the radiation time (5 min) were not much effective for water separation. This is because of the over boiling of the samples. Consequently, for microwave heating demulsification the best water separation efficiency was achieved at 3 (minutes), 360 (watt). Based on the result of microwave parameter’s calculations, it was found that parameters such as; dT/dt, Qmw, έ and ɛʺ, were inversely proportional to the radiation time. However, parameters such as λ and Dp were directly proportional to the time of the radiation.